The limits of economic complexity theory indicators for predicting the possibility of export diversification: a case study of Algerian exports - Larguet, Farida (Journal of Human Sciences, 2021)
Economic complexity theory has provided important concepts of the impact of the diversification and complexity of exports on the improvement of the future country’s income and growth. The theory builds its predictions on exports with a revealed comparative advantage. Application of the indicators of this theory to the Algerian economy has shown that the latter does not have significant productive capacities, and that its capacity to diversify and make future exports more complex is weak. On the other hand, application of the indicators of the International Trade Center has shown that a large number of Algerian products are moderately complex, and whose exports can be diversified. These results indicate that Algeria has production capabilities, which allow it to develop its future exports of moderately complex products. In conclusion, the fact that the predictions of the theory of economic complexity are based on exports of revealed comparative advantage limits the results of their application.